Memahami Kesulitan Belajar Anak Karena Gangguan Perkembangan - Habsy, Bakhrudin All; Nurjanah, Siti; Faradila, Ismi; Purnama, Ivan Fadilah Putra (Lembaga Yasin AlSys, 2024)
Conditions that affect a person's ability to develop normally are known as developmental disorders. The developmental disorders discussed in this study are Autism, ADHD and Down Syndrome. The purpose of this research is to find out the basic concepts of learning difficulties caused by developmental disorders. Through the analysis of the literature study, the researcher can draw conclusions regarding the definition of learning difficulties, defining developmental disorders, and to improve learning outcomes, learning disorders must be overcome. Learning disabilities need to be overcome to improve achievement in learning outcomes and give every individual the right to learn.